Ways to Increase Tax Collection - Abduraxmanovna, Berdieva Uguloy (American Journal of Economics and Business Management, 2025)
The role of taxes in ensuring economic stability of the country and the formation of the main sources of income of the state budget is invaluable. In particular, the correct and effective meeting of taxes - their accumulation is one of the key factors in the successful implementation of fiscal policy. This article will study ways systematically studied for the accumulation of tax accumulation in the Republic of Uzbekistan, the current tax policy is analyzed and its level of efficiency is assessed. Factors that ensure a stable increase in tax revenues during the study, including the widespread introduction of tax administration, measures to combat the hidden economy, and to combat the hidden economy, and the formation of an open communication environment with business entities, and the formation of an open communication with business entities. The article also introduces mechanisms used in the example of advanced foreign experience, which is considered to be analyzed, and their potential will be considered in Uzbekistan. Theoretical basis of the article is scientific studies related to fiscal policies, tax administration, public finances and economic reforms. On the basis of statistics and practical experiments, measures will be developed by the author, including measures to expand the tax base, optimize tax benefits and establish a fair distribution of tax order and strengthening tax discipline. This article is aoretical and practical significance for professionals, scientists, researchers, as well as professionals, and practical financial practices in the Republic of Uzbekistan, and servicemen, as well as the public financial.